If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + y = 10x + 100y Solving x + y = 10x + 100y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. x + -10x + y = 10x + -10x + 100y Combine like terms: x + -10x = -9x -9x + y = 10x + -10x + 100y Combine like terms: 10x + -10x = 0 -9x + y = 0 + 100y -9x + y = 100y Add '-1y' to each side of the equation. -9x + y + -1y = 100y + -1y Combine like terms: y + -1y = 0 -9x + 0 = 100y + -1y -9x = 100y + -1y Combine like terms: 100y + -1y = 99y -9x = 99y Divide each side by '-9'. x = -11y Simplifying x = -11y
| x+y=2x+3y | | 2x+3y=3x+2y | | 2x+3y^5=10x^2+5y^3 | | 2x^10+3y^5=10x^2+5y^3 | | 3x^2+1234098x^29=10y+29340y^92 | | (2h+3)(h-4)=13 | | 1234987+2348=230498 | | 3w+2x+2y-6(-2w+x-5y-3)=-32 | | 3x^2-4x=x^2-3x | | 6=(2*3) | | 3x-0.5=3x-1 | | y+12=21 | | =2*cos(2x) | | h(2)=3*2(6)+16 | | g(11)=27(11-48) | | 9-2(8x-9)=11x | | 5(10p-1)=150-20+65 | | h(-65)=-31(-65)-127 | | -5-4x=3 | | ln(x+9)-lnx=1 | | g(1)=e(1)-153 | | x^12-81= | | F(26)=3(26-26)-5 | | 4x+3y=26.50 | | 62X-1=7776 | | -6+2x=1+-7+3x+-1x | | g(0.5)=20*5(4*0.5) | | g(2)=3(2)-15 | | 2=7(5y-9)-5 | | h(2)=2*3(2(2)-2)+30 | | ln(x^2-3x+2)=0 | | 3k-1k=5-7k |